Characterization of bone mineral‐resembling biomaterials for optimizing human osteoclast differentiation and resorption. Issue 11 (30th March 2013) - Nakamura, Miho; Hentunen, Teuvo; Salonen, Jukka; Nagai, Akiko; Yamashita, Kimihiro
<x xml:space="preserve">Abstract</x> Bioresorption is a biological mechanism by which biomaterials are resorbed and thereby disappear from implantation sites partially or completely over a period of time. Osteoclast‐medicated bioresorption is a possible new advantage to incorporate material degradation into remodeling in bone metabolism process. The purpose of this study was to investigate the osteoclastogenesis and bioresorption of synthesized calcium phosphate materials. Differentiation into mature human osteoclasts on carbonated hydroxyapatite (CA) was significantly enhanced compared to hydroxyapatite (HA) and β‐tricalcium phosphate, based on the quantitative gene expressions of molecular markers for osteoclast differentiation. Osteoclasts adhered and differentiated into giant multinuclear TRAP‐positive cells on every type of synthesized sample based on the histological analysis. Morphological observations using fluorescence and quantitative analysis revealed that the actin rings of osteoclasts on CA were thick, small in diameter and co‐localized with vinculin, similar to the rings found on bone slices. In contrast, the actin rings of osteoclasts on HA and culture dishes were thin and large in diameter. Scanning electron microscopic images and quantitative analysis indicated that the resorption pits on CA were significantly deeper than those on HA due to the enhanced tight sealing ability between osteoclasts and their substrate. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3141–3151, 2013.